The effect of CultiVar and spraying with amino-alexin and trace elements and their interaction on some physiological characteristics and the Yield of two Varieties of cucumber (Cucumis sativus L.) grown in greenhouses. - Hala Adnan Shaheed, Hala Adnan Shaheed; Batool Hanoon Falih AL.zubaidy; Tariq Okla Hadros (University of Thi-Qar Journal of agricultural research, 2021)
this experiment was carried out in one of the unheated greenhouses at the station of the College of Agriculture and the Marshes / University of Thi Qar, Al-Mawhahiya area, during the autumn season 2019-2020, by designing a split split plot. The experiment included three treatments and three replicates, between two varieties of cucumber Jamela and Dats, three concentrations of trace elements (0, 20 and 40) gL - 1 and three concentrations of amino elxain (0,3.5 and 7) ml – 1 and the plants were sprayed. Three times, the first was at flowering, the second sprayed 15 days after the first spray, and the third sprayed 15 days after the second spray.This study aims to find out the effect of aminoxin and trace elements on the cucumber plant and study some of the physiological properties and yield and determine the best suitable hybrid that can be cultivated in the conditions of the southern region, especially Dhi Qar governorate. Total of leaves (mg. 100 gm -1 soft weight), free amino acid content of fruits (mg. Liter -1) and total yield of house (kg. Plastic house -1) when spraying with trace elements treatment which gave (6.687 mg, 100 gm -1 fresh weight, 2.2450 mg. Liters -1 and 43.908 kg. Plastic house -1), while when spraying with amino - xene, the highest rate was recorded (7.196 mg. 100 gm - 1) soft weight and 2.5011 mg. Liter - 1 and 38.475 kg. -1) While the comparison treatment recorded the lowest rate of these characteristics, and Jamela was superior to Dats in the content of amino acids and the total output of the house. As for the double and triple interactions, it was significant in these characteristics.